Spin-splitting and spin Hall effect of reflected Airy beams on the surface of topological insulator - Di Yu; Haoyuan Song; Yubo Li; Yuqi Zhang; Qiang Zhang; Shufang Fu; Xuanzhang Wang (Results in Physics, 2024)
We present an analysis of the enhanced spin Hall effect of light (SHEL) resulting from a reflected Airy beam off the interface of an air-topological insulator (TI). Our study suggests that the surface conductivity of TI film and the decay factors of Airy beams are crucial in increasing the spin-splitting distance and the spatial shifts of the left-handed circularly polarized (LCP) and right-handed circularly polarized (RCP) components. An apparent spatial shift asymmetry depending on the decay factors can be observed between the LCP and RCP components, where the coupling of intrinsic and extrinsic angular momentum will play a significant impact. The connection among the thickness of TI film, chemical potential and the incident frequency at the fixed decay factors is thoroughly examined to achieve the maximum of spatial shifts. We find that the coupling between the upper and lower surfaces’ conductivity could be responsible for the pronounced SHEL. These conclusions can be extended to other interfaces of comparable structures, such as insulators coated with a layer of two-dimensional Dirac material. Our work provides novel insights into the use of innovative beams incident on the surface of TI film and their potential applications in optical detection.